2019
DOI: 10.1108/yc-12-2018-0898
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of green product buying decision among young consumers in Malaysia

Abstract: Purpose This study aims to investigate the factors, which may potentially influence green product buying decision among young consumers in Malaysia. Design/methodology/approach A perceived lack of intention to buy green products observed among the Malaysian Generation Young consumers has sparked the interest to carry out this study. With the aid of structured questionnaires, data were collected from a total of 217 respondents, between 18 and 25 years of age. Findings The results of data analysis indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 53 publications
(75 reference statements)
5
59
0
16
Order By: Relevance
“…in recent times. Further, the young consumer also appears among the red-colored cluster of keywords indicating that authors are also exploring the linkage of green products with the strata of young consumers as confirmed by the available studies [ 78 , 79 ]. The above author keyword analysis shows that there has been a clear maturation in the field of research concerning green products from the early debates on sustainable design, green marketing, sustainable development, and sustainability.…”
Section: Bibliometric Analysis Of Literature: Resultsmentioning
confidence: 77%
“…in recent times. Further, the young consumer also appears among the red-colored cluster of keywords indicating that authors are also exploring the linkage of green products with the strata of young consumers as confirmed by the available studies [ 78 , 79 ]. The above author keyword analysis shows that there has been a clear maturation in the field of research concerning green products from the early debates on sustainable design, green marketing, sustainable development, and sustainability.…”
Section: Bibliometric Analysis Of Literature: Resultsmentioning
confidence: 77%
“…From an empirical perspective, Fu et al (2020) and Shen & Chen (2020) find out that environmental concern significantly affects purchase intention. Likewise, according to Tan et al (2019), increasing environmental concerns significantly affected the consumers' intention to buy green products. Several studies have confirmed a positive relationship between the individual's concern for the environment and their preferring green consumption (Sun et al, 2019).…”
Section: Green Concern and Green Attitudementioning
confidence: 99%
“…For DiscoTope, the propensity score radius was 22 Angstrom, upper half sphere radius was 14 Angstrom, window size was 1, and alpha was 0.115. An in-house script (DiscoTope2ChimeraAttr) has been utilized to convert DiscoTope result into Chimera attributes for visualization in 3D, with a default threshold DiscoTope score of −3.7 [40]. These analyses were done to pinpoint the specific immunogenic regions within the full-length proteins.…”
Section: B-cell Epitope Predictionmentioning
confidence: 99%